A TRANSNATIONAL STUDY ON AMERICAN HEGEMONY OF INDONESIAN MALE TEENAGERS THROUGH SMACKDOWN - Dhionisius Bambang Gumilang (Rubikon : Journal of Transnational American Studies, 2016)
SmackDown is one of the most phenomenal products of U.S. popular culture. It goes beyond its geographical borders to broadcast in each house in other countries. It caused several deaths and injuries to Indonesian children during 2006 followed by the banning of the program from airing nationally. It began re-airing through TV cable in 2011 and fanbase communities were established in three major big cities in Indonesia, which are Yogyakarta, Bandung, and Jakarta.This research represents the perception of SmackDown among Indonesian male teenagers ages 15-17 and its effects as well as the power of SmackDown over them. It uses a mixed method of quantitative and qualitative methods in a grounded research under Transnational American Studies related to hegemony and popular culture. The analysis of the data that are collected through quantitative method uses the semiotic approach that links the sign, signified, and signifiers to the reality by comparing it to the American perception based on the published journals, thesis, or dissertations to Indonesian perception from interviews and group discussions with fanbase members, students from three private high schools and athletes of amateur wrestling.This research reveals that hegemonic masculinity that constructs gender in society is shaped through the broadcast of SmackDown in Indonesia. It is seen from the performance that justifies violence, portrays the ideal body for men and positions women as inferior to men. Meanwhile, the SmackDown itself engages the audience by manipulating the reality in order to blur the line between fantasy and reality. The blurred lines give the audience a sense of pseudo-ideology which puts fantasy as their reality. Gender construction is pseudo-ideology to the society. Keywords: SmackDown, hegemony, popular culture, transnational